2022
DOI: 10.1093/mnras/stac1277
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing atmospheres of cloudy temperate mini-neptunes with JWST

Abstract: The upcoming James Webb Space Telescope (JWST) promises a generational shift in the study of temperate mini-Neptune atmospheres using transit spectroscopy. High-altitude clouds, however, threaten to impede their atmospheric characterization by muting spectral features. In this study, we systematically investigate JWST instrument configurations for characterizing cloudy mini-Neptune atmospheres, assessing the importance of instrument choice and wavelength coverage, focusing on NIRISS and NIRSpec. We consider tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…Several recent studies have demonstrated the feasibility of detecting key molecular signatures, including biomarkers, in candidate Hycean worlds using transit spectroscopy with JWST. 17,34,124 Our goal here is to assess (a) the spectral features of relevant chemical species observable with JWST transit spectroscopy, and (b) chemical diagnostics for identifying a Hycean planet.…”
Section: Observational Prospects With Jwstmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have demonstrated the feasibility of detecting key molecular signatures, including biomarkers, in candidate Hycean worlds using transit spectroscopy with JWST. 17,34,124 Our goal here is to assess (a) the spectral features of relevant chemical species observable with JWST transit spectroscopy, and (b) chemical diagnostics for identifying a Hycean planet.…”
Section: Observational Prospects With Jwstmentioning
confidence: 99%
“…We model a transmission spectrum of K2-18 b using an adaptation of the AURA exoplanet atmospheric modeling and retrieval code. 125 We refer the reader to previous works 17,124 for details on the model setup using the AURA code and for the same planet bulk parameters as considered here. The model considers a plane parallel atmosphere at the day-night terminator of the planet in hydrostatic equilibrium and computes the transmission spectrum for a given temperature structure and composition.…”
Section: Atmospheric Spectroscopy With Jwstmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider an isothermal pressure-temperature (P-T) profile with the temperature as a free parameter. Assuming a non-isothermal profile does not significantly influence the results and is not warranted given the data quality (also see, e.g., Constantinou & Madhusudhan 2022). Our baseline model therefore includes 12 free parameters: volume mixing ratios of the six molecules noted above (X i for i = H 2 O, CH 4 , NH 3 , CO, CO 2 , HCN), the isothermal temperature (T 0 ), the reference pressure (P ref ) corresponding to the planet radius of 2.19 R ⊕ derived from the broadband light curve (Table 1), and four cloud/haze parameters-the haze amplitude and slope (a and γ), cloud-top pressure (P c ), and cloud/haze covering fraction (f).…”
Section: Baseline Retrieval Assuming Uniform Stellar Brightnessmentioning
confidence: 99%
“…Future missions such as the James Webb Space Telescope (JWST) and Ariel (Tinetti et al 2018) will provide higher sensitivity and/or wider spectral coverage than HST/WFC3. This will have a huge impact on the detection of atmospheric features on small exoplanets, even with the presence of clouds at high altitudes (Hinkley et al 2022;Constantinou & Madhusudhan 2022;Whittaker et al 2022). If there is a significant amount of HCN in the atmosphere of L 98-59 b, we should be able to detect a very strong absorption feature near 2.5 µm, which is covered by the wavelength ranges of instruments from both of JWST and Ariel.…”
Section: Models With Clouds and Hazesmentioning
confidence: 99%